VIRTUAL REALITY FOR TOOTHBRUSHING TRAINING AMONG ELEMENTARY SCHOOL STUDENTS: A QUASI EXPERIMENTAL STUDY - Gina, Vrestylia Okta; Fadriyanti, Okmes; Ningrum, Valendriyani (Universitas Muhammadiyah Semarang, 2025)
Background: Virtual reality (VR) has emerged as a transformative tool in educational training across various fields, including dentistry. Several studies have shown that VR can enhance the transfer of skills learned in training to real-world applications. This study presents a virtual reality video intervention with horizontal toothbrushing technique. The aim is to assess the effect of an educational intervention program on toothbrushing practice among elementary students at public elementary school 10 in Padang City.Method: A quasi-experimental (pre-post) study design was conducted by 40 children with purposive sampling techniques. Pre-intervention and 4 weeks post-intervention assessments were conducted to assess the changes in the practices of toothbrushing properly. The measurement tool uses a 0–20-point scoring method. Wilcoxon's test was performed to investigate the differences between before and after intervention virtual reality toothbrushing training.Outcome: There was an increased performance of toothbrushing skills, mean score before intervention 9.5 (minimum 4, maximum 14 points) and after intervention 17.5 (minimum 12, maximum 20 points). A significant improvement was observed between before and after using virtual reality based toothbrushing training (p < 0.05) among study participants.Conclusion: Virtual reality-guided toothbrushing training could improve the toothbrushing skills of children. These findings suggested that virtual reality-based health promotion could be implemented among students at elementary school.